2021
DOI: 10.1038/s41531-021-00181-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed orthostatic hypotension in Parkinson’s disease

Abstract: Orthostatic hypotension (OH) is relatively common in the early stage of Parkinson’s disease (PD). It is divided into delayed OH and classical OH. Classical OH in PD has been investigated widely, however, the clinical implications of delayed OH in PD have seldom been studied. The purpose of this study is to characterize delayed OH in PD. A total of 285 patients with early drug-naïve PD were enrolled and divided into three groups according to orthostatic change: no-OH, delayed OH, and classical OH. The disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Orthostatic hypotension can cause syncope and falls 16 and fall-related fractures, pneumonia, and even death. Some autonomic symptoms, such as constipation, can occur in the early stage of disease and may even precede the onset of motor symptoms by many years 16 , 17 . We speculate that both dopaminergic and adrenergic neurons in the nigrostriatal and peripheral nervous systems are lost progressively with the gradual worsening of motor and non-motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Orthostatic hypotension can cause syncope and falls 16 and fall-related fractures, pneumonia, and even death. Some autonomic symptoms, such as constipation, can occur in the early stage of disease and may even precede the onset of motor symptoms by many years 16 , 17 . We speculate that both dopaminergic and adrenergic neurons in the nigrostriatal and peripheral nervous systems are lost progressively with the gradual worsening of motor and non-motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…2 PD + OH patients were slightly older and had a higher supine systolic BP compared to PD No-OH patients, as reported by previous studies. 9,15 This suggests that PD + OH patients could have suffered greater cerebral hemodynamic insult due to wider BP uctuations. 16 Each caudate nucleus was signi cantly correlated to multiple ipsilateral regions.…”
Section: Discussionmentioning
confidence: 99%
“…Falls can lead to injury, decreased activity due to fear of falling, poor quality of life, and caregiver stress ( LeWitt et al, 2019 ). Studies have shown that OH can happen in the early stages of the disease and may occur with or without symptoms ( Palma et al, 2015 ; Cutsforth-Gregory and Low 2019 ; Yoo et al, 2021 ). In this study, we investigated the involvement of the cardiac baroreflex and cardio-postural coupling (hypothesized reflex muscle-pump function) in maintaining blood pressure in Parkinson’s patients and healthy controls during an orthostatic challenge induced via a head-up tilt test.…”
Section: Introductionmentioning
confidence: 99%